26.2 miles to happiness a comedian's tale of running, red wine and redemption - Tonkinson, Paul (Bloomsbury Sport, 2020)
The hilarious trials and tribulations of stand-up comedian Paul Tonkinson as he attempts to beat the much lauded 3-hour mark at the London Marathon